THE INFLUENCE OF BASIC INFORMATION META-SYSTEMS ON THE FORMATION OF «HYPOCHONDRIACAL DISCOURSE» - Shebanova, Vitaliia (PSYCHOLOGICAL JOURNAL, 2018)
The article considers the influence of three basic information meta- systems on the formation of “hypochondriacal discourse”, “hypochondriacal body” and “hypochondriacal style of behavior”. Such components of hypochondriacal discourse as “prophylactic”, “health-improving” and “advertising” are presented. It is grounded that the fixation (as impulsive obsession to follow strictly any discourse) promotes the alienation of the body and the distortion of behavioral strategies up to their extreme variants (the pathology of corporeality of the somatopsychic or psychosomatic nature). It is proved that the subjective perception by the individual of his body as a source of harmful desires and as an object of transformations (doing exercises, cleansing treatment, and various dietary and cosmetic treatments, massage etc.) causes the alienation of the body (besides, the more unpleasant treatment performed on the body is, the deeper its alienation). It is described that for the people in a traumatic situation of “real or imaginary overweight on a background of chronic dissatisfaction”, “harmful food” consumption of which (from their point of view) causes “thick body” which must be combated (improved, corrected, modeled) is “the threat system”. It is proved that eating disorders (anorexia, bulimia, a psychogenic overeating, night eating syndrome etc.) are a part of the structure of hypochondriacal meta-syndromic formation, because they represent behavioral strategies, including eating behavior, the purpose of which (despite their disadaptive character) is directed at struggle with “the threats” and the achievement of physical comfort in accordance with “concern for the body” myth (as the internal subjective picture of life activity). The hypochondriatic discourse of modern cultural texts, on the one hand, directs the individual to an understanding of the value of his health and “self-care”, but on the other - contributes to excessive fixation of attention on certain aspects of the functioning of their own physicality, which significantly distorts the emphasis of life. One can predict that a person, under the influence of constant hypochondriatic anxiety (excess weight, general condition of his health, etc.), instead of realizing his own potential, is constantly disturbed and focused on the permanent observation and control over the subject of his fears (proper nutrition, the proper functioning of psychophysiological processes of your body, etc.). In other words, the livelihoods of the creative process turn into life support. Keywords: hypochondriacal discourse, information meta-system, the alienation of the body, eating disorders.